2005
DOI: 10.3168/jds.s0022-0302(05)73134-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Source and Amount of Crude Protein on the Intestinal Supply of Nitrogen Fractions and Performance of Dairy Cows

Abstract: The objective of this article was to review and summarize the significance of the amount and source of dietary crude protein supplements on the supply of nitrogen fractions passing to the small intestine and the performance of lactating dairy cows. A meta-analysis was used to evaluate 2 data sets, one for nitrogen flow to the small intestine and one for performance of cows. The response of dairy cows to rumen-undegradable protein supplements is variable. A portion of this variable response from research trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
78
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 174 publications
18
78
3
Order By: Relevance
“…Maximum milk yield was achieved at 23% CP in the diet. Similar results were reported by Ipharraguerre and Clark (2005a) using a larger data set (112 studies published from and different methodologies. They estimated increases in milk yield of 0.94 and 0.42 kg d -1 when dietary CP was increased from 15 to 16 and 19 to 20%, respectively.…”
Section: Introductionsupporting
confidence: 87%
“…Maximum milk yield was achieved at 23% CP in the diet. Similar results were reported by Ipharraguerre and Clark (2005a) using a larger data set (112 studies published from and different methodologies. They estimated increases in milk yield of 0.94 and 0.42 kg d -1 when dietary CP was increased from 15 to 16 and 19 to 20%, respectively.…”
Section: Introductionsupporting
confidence: 87%
“…In the EGS treatment, the animals that received RUP had higher milk production than those that received RDP, which may be associated with a higher availability of amino acids in the small intestine from digesting the protein that escaped microbial degradation in the rumen (Broderick, 2003). Huhtanen and Hristov (2009) and Ipharraguerre and Clark (2005) found that raising RUP levels of the diet is not necessarily associated with positive increments in milk production. Huhtanen and Hristov (2009) stated that one of the possible causes of these inconsistent responses to elevated dietary RUP levels may be related to an excess of metabolizable protein supply, i.e., in excess of the amount required.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal HC inclusion observed in this study (Figure 1) had a CP concentration that was similar to the 165 g/kg DM resulting in maximum yields of milk (38.3 kg/day) and milk protein (1.18 kg/day) in a study by Olmos Colmenero and Broderick (2006). A meta-analysis by Ipharraguerre and Clark (2005) shows a significant curvilinear relationship (R 2 5 0.19) between milk yield and the CP concentration in the diet (ranging from 121 to 258 g/kg DM), but they reported the highest milk yield at a much higher CP concentration of 230 g/kg DM.…”
Section: Milk Yield and Compositionmentioning
confidence: 99%
“…Increasing dietary CP often gives a curvilinear response with respect to milk production (e.g. Ipharraguerre and Clark, 2005) and a linear decrease in N efficiency (e.g. Olmos Colmenero and Broderick, 2006;Huhtanen and Hristov, 2009).…”
Section: Introductionmentioning
confidence: 99%